(untitled) (Quinto Sol, 2023)
The article analyzes the consolidation process in Brazil of an agrarian administration that required scientific and professional training of technical cadres in rural issues between 1930-1955 and sought to understand objectives of the Brazilian government in increasing techno-scientific cooperation in agrarian matters in the context South-South in those years. Through the documentary analysis of the Ministries of Agriculture and Foreign Relations of Brazil, it was noted that this political orientation was articulated with the growing need of the countries of the region to have technical and scientific support in tropical and subtropical crops, both for supplying internally as well as to strengthen their own markets in the face of the scenario that emerged with the Great World Wars. Under Tore Olsson’s concept of agrarian crossings, scientific exchanges in agricultural and veterinary matters were analyzed, especially in livestock and wheat cultivation, as well as the dissemination of agrarian knowledge, technical advisory missions, and also the action of research institutes that sought to both expand technical cooperation and secure Brazilian geopolitical interests on the continent.